2021
DOI: 10.1177/10105395211041001
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Food Intake of Indonesian Children Under 5 Years of Age: A Systematic Review

Abstract: The Indonesian Government’s targets to reduce the prevalence of child malnutrition are unlikely to be met based on current progress. Adequate dietary intake is key to meeting these targets. This systematic review aimed to provide a comprehensive overview of the nutrient and food intake of Indonesian children under 5 years of age. Peer-reviewed and gray literature published between 2007 and 2019 were collected. Of 1500 records, 38 articles met the study inclusion criteria and a narrative analysis was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…In contrast, while the low consumption of nutrient-rich foods is an issue, a significant proportion of both urban and rural children in Indonesia and India are consuming energy-dense/nutrient‐poor snacks and SSBs already during the CF period—between 6 and 24 mo. A previous review from Indonesia indicated that nearly all children under 5 y of age consumed snacks daily ( 96 ). However, the consumption of energy-dense/nutrient‐poor snacks or SSBs during the CF period was not reported by other reviews ( 34 , 51 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, while the low consumption of nutrient-rich foods is an issue, a significant proportion of both urban and rural children in Indonesia and India are consuming energy-dense/nutrient‐poor snacks and SSBs already during the CF period—between 6 and 24 mo. A previous review from Indonesia indicated that nearly all children under 5 y of age consumed snacks daily ( 96 ). However, the consumption of energy-dense/nutrient‐poor snacks or SSBs during the CF period was not reported by other reviews ( 34 , 51 , 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on children’s nutrient intakes in Indonesia, but an adequate summary of nutrient inadequacies was challenging for Arini and colleagues to provide, due to the heterogenicity in subject characteristics among studies ( 3 ). In this study, data were derived from Indonesian 2014 Food Intake Survey, a national representative survey.…”
Section: Discussionmentioning
confidence: 99%
“…Better dietary intake is one of the key aspects to improve the situation. A systematic review showed that in children under-5 years in Indonesia, micronutrient intake varied, for example iron ranged from 2.40 to 12.8 mg/d, zinc ranged from 1.20 to 5.53 mg/d, calcium ranged from 83 to 707.9 mg/d, vitamin A ranged from 53 to 1,335 ug/d, and vitamin D ranged 2.75–14.10 ug/d ( 3 ). Prevalence of micronutrient deficiency in children under-five was also reported in a national survey, such as anemia (urban 17.6% vs. rural 18.5%), iron deficiency (urban 4.6% vs. rural 8.8%), and vitamin D deficiency (urban 43% vs. rural 44.2%) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that factors other than protein inadequacy may be contributing to child malnutrition in Indonesia. The mixed reporting of energy and macronutrient intake also suggests that undernutrition in Indonesian children is not solely caused by inadequate macronutrient consumption, but is likely linked to deficiencies in essential micronutrients, which are not regularly assessed or reported [18].…”
Section: Resultsmentioning
confidence: 99%